Investigation into Mg-4.5Al-2.5Zn Mg alloy applying cryogenic treatment and cross-rolling at diverse temperatures - Haoran Pang; Liwei Lu; Rui Yang; Min Ma; Xiaojun Wang; Yujuan Wu; Lei Jing; Jun Dong; Shaowei Zhang (Journal of Materials Research and Technology, 2025)
In the paper, the Mg-4.5Al-2.5Zn plates were processed by cryogenic treatment after cross-rolling with different temperatures to explore the impact of cross-rolling temperatures and cryogenic treatment on microstructure and mechanical properties. Electron backscatter diffraction (EBSD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM) were used to analyze the mechanisms. The results demonstrate that the cryogenic treatment after cross-rolling can improve the mechanical properties and microstructure of Mg-4.5Al-2.5Zn alloy. With the rising of hot rolling temperature, the strength and ductility increase firstly and then decrease. The sample processed by cryogenic treatment after hot cross-rolling at 370 °C presents the highest strength (∼305.6 MPa) and ductility (∼17 %), which can be ascribed to fine grains, relatively high dislocation density, precipitates and weak basal texture. In this sample, the average grain size can be refined to 3.4 μm due to high extent dynamic recrystallization (DRX) caused by high density dislocation and grain boundary migeration, some Al8Mn5 precipitates distributed along grain boundaries, pinning the grain boundary. Weakening of the basal texture is concerned with the activation of prismatic slip, pyramidal slip and pyramidal <c+a> slip and the change of orientation of grain.